α‐Synuclein Pathology Spreads in a Midbrain–Hindbrain Assembloid Model - Gemma Gomez‐Giro; Daniela Frangenberg; Daniela Vega; Alise Zagare; Kyriaki Barmpa; Paul M. A. Antony; Graham Robertson; Rahman Sabahi‐Kaviani; Kristian Haendler; Nathalie Kruse; Florentia Papastefanaki; Rebecca Matsas; et al. (Advanced Science)
Abstract Understanding the progression of α‐synuclein pathology in neurodegenerative diseases such as Parkinson's disease (PD) is a longstanding challenge. Here, a novel midbrain–hindbrain‐assembloid model that recapitulates the spread of α‐synuclein pathology observed in PD patients, akin to Braak's hypothesis, is presented. Initially, the presence α‐synuclein pathology is demonstrated in the hindbrain organoids. Subsequently, sophisticated tissue engineering methods are employed to create midbrain–hindbrain assembloids. These assembloids allow investigation and description of the spreading of α‐synuclein pathology, as it progresses from the hindbrain components to the midbrain regions within the integrated structure. It is observed that an increase in α‐synuclein in the hindbrain can induce transfer of the pathology into the healthy midbrain, as well as cause changes at the synapse level. The presented model constitutes a robust in vitro platform for investigating the mechanisms underlying α‐synuclein spreading and disease progression, and holding potential for the screening of prospective therapeutics targeting the pathological propagation in PD and related synucleinopathies.